2008
DOI: 10.1303/aez.2008.599
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and insecticidal potential of essential oils from Egyptian plants against Sitophilus oryzae (L.) (Coleoptera: Curculionidae) and Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae)

Abstract: Essential oils of eight plants growing in Egypt were isolated by hydrodistillation. The chemical composition of the isolated oils was examined by gas chromatography/mass spectrometry (GC-MS). In the contact toxicity assay, the oils of Mentha microphylla and Artemisia judaica were the most potent against Sitophilus oryzae. When tested against Tribolium castaneum, the oils of M. microphylla, Eucalyptus camaldulensis and A. judaica showed the highest activity among the test oils with M. microphylla being the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 42 publications
(41 reference statements)
4
47
3
Order By: Relevance
“…On the other hand, the major constituents of the essential oils isolated from A. monosperma, O. vulgare, T. occidentalis and A. judaica were completely differed with those previously reported on the chemistry of these oils (Şahin et al, 2004;Mohamed and Abdelgaleil, 2008;Tsiri et al, 2009;Khan et al, 2012). Some of the major constituents of the essential oils of P. tortuosus, V. agnus-castus, S. terebinthifolius and S. cumini were similar to those previously reported for the oils isolated from plants growing in Egypt and other countries around the world (Singab et al, 2003;Gundidza et al, 2009;Stojković et al, 2011).…”
Section: Effect Of Essential Oils On E Crusgalli Seedling Growthcontrasting
confidence: 60%
“…On the other hand, the major constituents of the essential oils isolated from A. monosperma, O. vulgare, T. occidentalis and A. judaica were completely differed with those previously reported on the chemistry of these oils (Şahin et al, 2004;Mohamed and Abdelgaleil, 2008;Tsiri et al, 2009;Khan et al, 2012). Some of the major constituents of the essential oils of P. tortuosus, V. agnus-castus, S. terebinthifolius and S. cumini were similar to those previously reported for the oils isolated from plants growing in Egypt and other countries around the world (Singab et al, 2003;Gundidza et al, 2009;Stojković et al, 2011).…”
Section: Effect Of Essential Oils On E Crusgalli Seedling Growthcontrasting
confidence: 60%
“…The results showed that both species have larvicidal potential: L. camara with LC50 of 42.3±0.85 µg/mL, and L. montevidensis with LC50 of 117±0.5 µg/mL. The essential oil also showed insecticidal activity against adults of Sitophilus oryzae L. (LC50 0.22 mg/cm 2 ) and Tribolium castaneum (LC50 0.22 mg/cm2), and revealed low fumigant toxicity against S. oryzae (LC50 29.47 µL/L) and against T. castaneum (LC50 47.68 µL/L) (Mohamed & Abdelgaleil, 2008). Kumar & Maneemegalai (2008) investigated the methanol and ethanol extracts of leaves and flowers of L. camara L. and showed mosquito larvicidal activity against 3 rd and 4 th instar larvae of the mosquito species A. aegypti and C. quinquefasciatus.…”
Section: Insecticidal Activitymentioning
confidence: 96%
“…The highest insecticidal activity of Mentha microphylla might refer to the chemical ingredients of the leaves (i.e. menthone and piperitone) which are physiologically active chemicals and have been used in insecticide manufacturing [39]. Besides, piperitone oxide possess antibacterial and antifungal activity [40].…”
Section: Mortality Of Tribolium Castaneum Larvaementioning
confidence: 99%
“…The botanical extracts exhibited more insecticidal toxicity against T. castaneum than to C. maculates and S. zeamais [42]. [43] observed during laboratory experiment that highest insecticidal activity recorded via Mentha microphyla oil extract on Tribolium castaneum and Sitophilus oryzae, followed by Eucalyptus camaldulensis within eight different plant extracts. Wherease in another study, Mentha microphyla showed similar toxicity to both T. castaneum and S. oryzae [39].…”
Section: Mortality Of Tribolium Castaneum Larvaementioning
confidence: 99%